Gender diversity and earnings management: Evidence from Bangladesh (IIUC Business Review, 2022)
This study aims to evaluate the impact of Gender-diversity on earnings manipulation using both accrual and real earnings management techniques. All the data has been gathered from yearly reports of recorded non-financial organizations in Bangladesh from 2011 to 2019; after necessary diagnostic checking, this study finally uses the OLS regression model to evaluate the relationship. Findings show that the non-financial organizations of Bangladesh are practicing both forms of earnings management simultaneously. Evidence illustrates that female directors on the board have no significant association with any proxies of accrual earnings management but are significantly positively associated with abnormal discretionary expenses. Moreover, the gender diversity of CEOs is negatively connected with abnormal production costs and positively associated with abnormal cash flow from operating activities, and the relationship is statistically significant. Policymakers and other stakeholders can use these findings to give more concentration on the issue of women's involvement at the corporate level and the development of governance issues.IIUC Business Review Vol. 9, Dec. 2020 pp. 111-133